2013
DOI: 10.1016/j.ultsonch.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound frequency and acoustic amplitude on the size of sonochemically active bubbles – Theoretical study

Abstract: Numerical simulation of chemical reactions inside an isolated spherical bubble of oxygen has been performed for various ambient bubble radii at different frequencies and acoustic amplitudes to study the effects of these two parameters on the range of ambient radius for an active bubble in sonochemical reactions. The employed model combines the dynamic of bubble collapse with the chemical kinetics of single cavitation bubble. Results from this model were compared with some experimental results presented in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(83 citation statements)
references
References 24 publications
3
80
0
Order By: Relevance
“…It is therefore wise to venture into knowing the impact each field -frequency and power of ultrasound, time of experiment, nature and concentration of solution etc. have on the overall process [49]- [51]. Only upon gaining the necessary intuition can a clear and analytical mind be set to logically understand the materials formed.…”
Section: ‫ݔ(ܲ‬ ‫)ݐ‬ = ‫ܣ‬ ‫ݐ߱(ݏܿ‬ − ‫ݔߚ‬ + ߮) -----(3)mentioning
confidence: 99%
“…It is therefore wise to venture into knowing the impact each field -frequency and power of ultrasound, time of experiment, nature and concentration of solution etc. have on the overall process [49]- [51]. Only upon gaining the necessary intuition can a clear and analytical mind be set to logically understand the materials formed.…”
Section: ‫ݔ(ܲ‬ ‫)ݐ‬ = ‫ܣ‬ ‫ݐ߱(ݏܿ‬ − ‫ݔߚ‬ + ߮) -----(3)mentioning
confidence: 99%
“…Moreover, it has recently been reported that the acoustic amplitude affects the range of ambient bubble radius for the production of HO • radical and the higher the acoustic amplitude was, the higher was the range of active bubbles for the production of the oxidants. 39 This implies that higher acoustic amplitude yields a higher number of bubbles and this leads to a higher concentration of • OH radicals in the dye solution. Consequently, the results of an increase in power intensity are greater sonochemical effects on microscopic and macroscopic scales (bubble and solution, respectively), resulting in higher BR29 degradation rates.…”
Section: Effect Of Power Intensitymentioning
confidence: 99%
“…As expected, the results showed that the increasing ultrasonic power significantly reduced the extraction time and obtained the highest extraction yield. It might be mainly attributed to the reason that an increase in ultrasonic power can provide more intense acoustic cavitation, which can markedly influence the acoustic amplitude and the dynamics of cavitation bubbles [30,31], and further can affect the extraction efficiency. As a result, the increase of ultrasonic power is beneficial to shorten the extraction time and to enhance the extraction yield.…”
Section: Effect Of Ultrasonic Powermentioning
confidence: 99%